Analysis of the Impact of Liquidity Policy and Economic Fluctuations on Asset and Wealth Management in the Banking Sector in Indonesia - Judijanto, Loso; Wijaya, Ismed; Sudarmanto, Eko (West Science Interdisciplinary Studies, 2024)
This study analyzes the impact of liquidity policy and economic fluctuations on asset and wealth management in the Indonesian banking sector. Utilizing a quantitative approach, data were collected from 150 banking professionals through a structured questionnaire and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) version 3. The results demonstrate that economic fluctuations significantly impact both asset and wealth management, with a stronger influence on wealth management. Liquidity policy also plays a crucial role in improving asset and wealth management practices, though its impact is moderate compared to economic fluctuations. These findings suggest that banks must adopt robust liquidity management and risk mitigation strategies to navigate periods of economic uncertainty and optimize asset and wealth management practices. The study provides important insights for banking professionals and policymakers aiming to enhance financial stability and operational efficiency in the banking sector.